2018
DOI: 10.1101/430819
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The sleep gene insomniac ubiquitinates targets at postsynaptic densities and is required for retrograde homeostatic signaling

Abstract: 27The nervous system confronts challenges during development and experience that can 28 destabilize information processing. To adapt to these perturbations, synapses homeostatically 29 adjust synaptic strength, a process referred to as homeostatic synaptic plasticity. At the 30 Drosophila neuromuscular junction, inhibition of postsynaptic glutamate receptors activates 31 retrograde signaling that precisely increases presynaptic neurotransmitter release to restore 32 baseline synaptic strength. However, the nat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 119 publications
0
2
0
Order By: Relevance
“…A recent study also found that AZ remodeling is blocked in brp mutants but that rapid PHP is expressed (Böhme et al, 2019). This implies other mechanisms, such as phosphorylation or ubiquitination, are necessary to express rapid PHP (Hauswirth et al, 2018; Kikuma et al, 2018 Preprint ; Wentzel et al, 2018). Over chronic timescales, however, the sustained expression of PHP requires both arl8 and brp (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study also found that AZ remodeling is blocked in brp mutants but that rapid PHP is expressed (Böhme et al, 2019). This implies other mechanisms, such as phosphorylation or ubiquitination, are necessary to express rapid PHP (Hauswirth et al, 2018; Kikuma et al, 2018 Preprint ; Wentzel et al, 2018). Over chronic timescales, however, the sustained expression of PHP requires both arl8 and brp (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We have presented evidence for a mirrored process across the presynaptic terminals of individual neurons, where the abundance of AZ material is adaptively scaled to maintain stable synaptic strength. These pre- and postsynaptic processes could work independently or in conjunction to adapt to altered innervation (Davis and Goodman, 1998; Branco et al, 2008; Tokuoka and Goda, 2008), excitability (Murthy et al, 2001; Paradis et al, 2001), activity (Butz et al, 2009; Holtmaat and Svoboda, 2009), injury (Goel and Dickman, 2018), and even sleep (Bushey et al, 2011; Hengen et al, 2016; Diering et al, 2017; Kikuma et al, 2018 Preprint ). The complex interplay of Hebbian and homeostatic regulation operating locally and globally, over distinct spatiotemporal scales and at both pre- and postsynaptic compartments, endows synapses with this astonishing combination of flexibility and stability.…”
Section: Discussionmentioning
confidence: 99%